2015
DOI: 10.1007/s11356-015-5316-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the position of insulating materials in flat roofs exposed to sunshine to gain minimum heat into buildings under periodic heat transfer conditions

Abstract: Building roofs are responsible for the huge heat gain in buildings. In the present work, an analysis of the influence of insulation location inside a flat roof exposed directly to the sun's radiation was performed to reduce heat gain in buildings. The unsteady thermal response parameters of the building roof such as admittance, transmittance, decrement factor, and time lags have been investigated by solving a one-dimensional diffusion equation under convective periodic boundary conditions. Theoretical results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…), as it simultaneously takes into account the thermal conductivity, the specific heat capacity, and the density, under periodic thermal conditions. A lower unsteady-state thermal transmittance value signifies a higher thermal resistance and thermal mass [39][40][41][42][43]. e steady-state thermal transmittance U s indicates the heat transfer rate through a building configuration.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…), as it simultaneously takes into account the thermal conductivity, the specific heat capacity, and the density, under periodic thermal conditions. A lower unsteady-state thermal transmittance value signifies a higher thermal resistance and thermal mass [39][40][41][42][43]. e steady-state thermal transmittance U s indicates the heat transfer rate through a building configuration.…”
Section: Analytical Methodologymentioning
confidence: 99%
“…For example, the thermal interdependencies between building zones could be derived from a wall's thermal admittance [141] and its materials. These parameters determine a wall's decrement delay (time lag between the timing of the temperature peaks at either of the wall's sides) and its decrement factor (dampening the temperature peak of one side of the wall to the other) [142]. That information should lead to the appropriate history lengths and inter-feature lags.…”
Section: Feature Selectionmentioning
confidence: 99%
“…In their proposal, they considered the unstable thermal response of the building roof, such as admittance, transmittance, decay factor, and time delays, through a one-dimensional diffusion equation under convective periodic boundary conditions. The theoretical compared with the experimental results of four types of walls are available in the literature [16].…”
Section: Introductionmentioning
confidence: 99%
“…The proposal was tested for three buildings characteristic of the existing building heritage. The results showed that the behavior of the three envelopes differs greatly because they interact in unique ways according to In the literature, there are many studies on the optimal insulation in walls; for example, Shaik and Talanki [16] analyzed the influence of insulation location within a flat roof directly exposed to solar radiation to reduce the heat gain in buildings. In their proposal, they considered the unstable thermal response of the building roof, such as admittance, transmittance, decay factor, and time delays, through a one-dimensional diffusion equation under convective periodic boundary conditions.…”
Section: Introductionmentioning
confidence: 99%